The worldwide impact of COVID-19 on cancer care: A meta-analysis of surveys published after the first wave of the pandemic - Di Cosimo, Serena; Susca, Nicola; Apolone, Giovanni; Silvestris, Nicola; Racanelli, Vito (Frontiers in Oncology, 2022)
Background: The rapid and global spread of COVID-19 posed a massive challenge to healthcare systems. They came across the need to provide high-intensity assistance to thousands of patients suffering from SARS-CoV-2 infection while assuring continuous care for all other diseases. This has been of particular importance in the oncology field. This study explores how oncology centers responded to the pandemic at a single center level by assessing surveys addressing different aspects of cancer care after the pandemic outbreak. Methods: We performed a systematic review and meta-analysis of the cancer care surveys published until December 11th, 2020. Data were analyzed according to three main areas of interest, namely health care organization, including cancellation/delay and/or modification of scheduled treatments, cancellation/delay of outpatient visits, and reduction of overall cancer care activities; routine use of preventive measures, such as personal protective equipment (PPE) by both patients and health care workers, and systematic SARS-CoV-2 screening by nasopharyngeal swabs; and implementation of telemedicine through remote consultations. Findings: Fifty surveys reporting data on 9150 providers from 121 countries on 5 continents were included. Cancellation/delay of treatment occurred in 58% of centers; delay of outpatient visits in 75%; changes in treatment plans in 65%; and a general reduction in clinical activity in 58%. Routine use of PPE by patients and healthcare personnel was reported by 81% and 80% of centers, respectively; systematic SARS-CoV-2 screening by nasopharyngeal swabs was reported by only 41% of centers. Virtual visits were implemented by the majority (72% of centers). Interpretation: These results describe the negative impact of COVID-19 on cancer care, the rapid response of cancer centers in terms of preventive measures and alternative treatment approaches such as telemedicine, and confirm that surveys can provide the valuable, low-cost and immediate information that critical situations require. Funding: There was no funding source.